Facet‐Dependent Phase Control by Band Filling and Anisotropic Electron–Lattice Coupling in HVO2 Epitaxial Films. (13th June 2018) - Yoon, Hyojin; Park, Jaeseoung; Choi, Si‐Young; Lee, Donghwa; Son, Junwoo
Abstract: Unlike the substitutional dopants, interstitial hydrogen effectively supplies significant amount of carriers in the empty narrow d band in correlated electronic systems by reversibly adding it into interstitial sites. Here, it is demonstrated that hydrogenated VO2, a heavily hydrogenated correlated insulating phase with 3d 2 electronic configuration, can be thermodynamically stabilized by topotactically preserving its lattice framework regardless of the facet direction of VO2 epilayers. However, the kinetics of phase modulation and the response of out‐of‐plane lattice expansion are clearly affected by the orientation of the crystal facet, which is attributed to the anisotropy in the diffusion of hydrogen atoms and to anisotropic expansion induced by chemical stress. This result demonstrates universal electron‐doping‐induced phase transition near‐integer numbers of d band filling in correlated electronic systems and also supports the idea that orientation of crystallographic facets can be exploited to control the rate of electronic phase transition and the degree of electron–lattice coupling. Abstract : The kinetics of phase modulation to HVO2, a heavily hydrogenated correlated insulating phase, and its lattice response are affected by the orientation of the crystal facet. This result supports the idea that orientation of crystallographic facets can be exploited to control the rate of electronic phase transition and the degree of electron–lattice coupling in correlated materials for Mottronics.